Koli fisherwoman engage in door-to-door sales - Mumbai Archive Project Team (Jio Institute, 2024)
Some Koli fisherwomen engage in door-to-door sales, walking through neighbourhoods with baskets of fresh fish to sell to residents. This direct approach allows them to reach customers who may not be able to visit the local fish market.